Нефтегазообразование в отложениях доманиковского типа - Неручев С. Г.; Рогозина Е. А.; Парпарова Г. М.; Зеличенко И. А.; Неручев С. Г. Сергей Германович (Ленинград, Недра, 1986)
Авт. указаны на обороте тит. л.